2007
DOI: 10.1111/j.1600-0870.2007.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: coordinating paleoclimate research on tropical cyclones with hurricane-climate theory and modelling

Abstract: A B S T R A C T Extending the meteorological record back in time can offer critical data for assessing tropical cyclone-climate links. While paleotempestology, the study of ancient storms, can provide a more realistic view of past 'worst case scenarios', future environmental conditions may have no analogues in the paleoclimate record. The primary value in paleotempestology proxy records arises from their ability to quantify climate-tropical cyclone interactions by sampling tropical cyclone activity during pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 68 publications
1
46
0
Order By: Relevance
“…In this method, the GCM supplies boundary and initial conditions to the regional model, which produces its own climatology of tropical cyclones. This approach has been applied so far to idealized climate change scenarios (Knutson et al 1998;Knutson and Tuleya 2004), to the climate of the late twentieth century (Knutson et al 2007), and most recently to future climates affected by global warming (T. Knutson 2007, personal communication). This last study drove a regional model of the tropical North Atlantic with a large-scale environment created by averaging the output of 18 GCMs used for the most recent report of the Intergovernmental Panel on Climate Change (IPCC).…”
Section: Doi: 101175/bams-89-3-347mentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, the GCM supplies boundary and initial conditions to the regional model, which produces its own climatology of tropical cyclones. This approach has been applied so far to idealized climate change scenarios (Knutson et al 1998;Knutson and Tuleya 2004), to the climate of the late twentieth century (Knutson et al 2007), and most recently to future climates affected by global warming (T. Knutson 2007, personal communication). This last study drove a regional model of the tropical North Atlantic with a large-scale environment created by averaging the output of 18 GCMs used for the most recent report of the Intergovernmental Panel on Climate Change (IPCC).…”
Section: Doi: 101175/bams-89-3-347mentioning
confidence: 99%
“…Proxies used so far include storm-driven overwash deposits in near-shore lakes and marshes (Liu and Fearn 1993;Donnelly and Woodruff 2007), oxygen isotopic anomalies recorded in speleothems (Malmquist 1997;Frappier et al 2007) and tree rings (Miller et al 2006), and storm-driven beach deposits (Nott 2003). Reconstructions of coastal tropical cyclone activity, some of which now extend over thousands of years, are beginning to reveal patterns of variability on decadal-to-centennial time scales (Liu and Fearn 1993;Donnelly and Woodruff 2007).…”
Section: Doi: 101175/bams-89-3-347mentioning
confidence: 99%
“…Moreover, there is significant interest in the field of paleotempestology to understand the conditions that affected the prehistoric record of TCs revealed by geologic proxies. While some widely used methods [e.g., Liu and Fearn, 1993;Donnelly and Woodruff, 2007;Frappier et al, 2007] provide data only for the most recent millennia (for which sedimentary records of overwash from barrier islands are available), nascent techniques using deep-sea cores recovered from sloping banks near the Florida current show the potential to uncover records back to earlier periods [Toomey et al, 2013]. Furthermore, some understanding (even qualitative) of the behavior of TCs during glacial periods would be useful to geologists, who have shown that tropical storms affected the geological evolution of islands in the western Pacific [Galewsky et al, 2006;Lin et al, 2008;Hayakawa and Takashi, 2009;Woodruff et al, 2009;Stark et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it was pointed out that paleorecords for tropical cyclone activity are still primarily based on hurricane-induced overwash deposits preserved within back-barrier environments. Contributors pointed toward many new emerging proxies for tropical cyclone activity, which include, but are not limited to, negative oxygen isotope (6 ls O) anomalies in stalagmites, tree rings, corals, and ostracods; event layers deposited within inland lakes; storm-induced beach ridges; and preserved offshore beds and bedforms (as discussed in Frappier et al 2007). Many of the processes involved in producing these geologic markers are still poorly understood and require study at a basic mechanistic level.…”
Section: When: 8-10 July 2008mentioning
confidence: 99%